Specific Sciences are More Important than the Humanities in the Education System - Fayzullayeva Shahzoda Akmalovna (International Journal on Orange Technologies, 2020)
For the development of the education system, subjects must be selected and taught. Therefore, it is important to include more of the most important subjects in the curriculum. The exact sciences are important for the development of the country. The humanities affect the psyche of the individual, while the exact sciences affect themind.Of course, the humanities are also important. But today the importance of the exact sciences is high. The process of globalization is unimaginable without the exact sciences